2013
DOI: 10.4236/aer.2013.14011
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional evidence for two separate oligosaccharide binding sites of Pasteurella multocida hyaluronan synthase

Abstract: Pasteurella multocida hyaluronan synthase (PmHAS) is a bi-functional glycosyltransferase, containing a β1,3-glucuronyltransferase and β1,4-N-acetylglucosaminetransferase domain. PmHAS catalyzes the elongation of hyaluronan (HA) through the sequential addition of single monosaccharides to the non-reducing end of the hyaluronan chain. Research is focused on the relation between the length of the HA oligosaccharide and the single-step elongation kinetics from HA 4 up to HA 9. It was found that the turnover number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In contrast, some of the GlmU and HyaD binding pockets were at the catalytic sites. HyaD also contains two active sites: one site has glucuronic acid-transferase activity, which elongates UDPglucuronic acid to oligosaccharides, and the other site has glucosamine-1-P-transferase activity, which prolongs UDP-N-acetyl-D-glucosamine to oligosaccharides [35]. Surface variation in the binding sites of the HyaD protein in this study was consistent with previous studies that identi ed the enzymatic binding site in the glucuronic acid-transferase domain of HyaD [35].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, some of the GlmU and HyaD binding pockets were at the catalytic sites. HyaD also contains two active sites: one site has glucuronic acid-transferase activity, which elongates UDPglucuronic acid to oligosaccharides, and the other site has glucosamine-1-P-transferase activity, which prolongs UDP-N-acetyl-D-glucosamine to oligosaccharides [35]. Surface variation in the binding sites of the HyaD protein in this study was consistent with previous studies that identi ed the enzymatic binding site in the glucuronic acid-transferase domain of HyaD [35].…”
Section: Discussionsupporting
confidence: 89%
“…HyaD also contains two active sites: one site has glucuronic acid-transferase activity, which elongates UDPglucuronic acid to oligosaccharides, and the other site has glucosamine-1-P-transferase activity, which prolongs UDP-N-acetyl-D-glucosamine to oligosaccharides [35]. Surface variation in the binding sites of the HyaD protein in this study was consistent with previous studies that identi ed the enzymatic binding site in the glucuronic acid-transferase domain of HyaD [35]. Our study found that the arrangement of DUF2536 and TPR_2 repeats in the HyaD protein differed in these P. multocida strains, suggesting the reason for the structural variation of the binding site and perhaps different molecular activities.…”
Section: Discussionmentioning
confidence: 99%
“…pmHAS has been expressed and successfully synthesised HA in a number of bacterial species, including E. coli (Liu et al 2011 ; Mao and Chen 2007 ; Mao et al 2009 ). Since then this enzyme has become a focal point for cell-free HA production as its truncated form (pmHAS1-703) does not need to be bound to a membrane in order to synthesise HA (DeAngelis et al 1998 ; Jing and DeAngelis 2003 , 2004 ; Kooy et al 2013 ).…”
Section: Ha Synthase (Has)mentioning
confidence: 99%
“…A model of the core pmHAS‐WT 72–688 has already been reported by Kooy and co‐workers . In our model, we completed the C‐terminal portion of the core synthase and improved the N‐terminal domain by further extending it by 40 residues.…”
Section: Resultsmentioning
confidence: 99%
“…This corroborates that domain A1 confers GlcNAc‐transferase activity . Lastly, pmHAS catalyses the sequential elongation of HA at the nonreducing end of the nascent HA polymer, with its β1,3‐glucuronyltransferase and β1,4‐ N ‐acetylglucosaminyltransferase domains working synergistically as one polypeptide . Due to the processive mechanism of HA polymerisation, it is concluded that, apart from the two UDP sugar binding sites, two other HA binding sites exist in pmHAS .…”
Section: Introductionmentioning
confidence: 99%